THE CORRELATION BETWEEN SELF-CONFIDENCE AND SPEAKING PERFORMANCE OF THE FOURTH SEMESTER STUDENTS OF ENGLISH DEPARTMENT OF UNIVERSITY OF ISLAM MALANG (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2019)
Abstract: Speaking is a productive skill which leads the ones have an effective communication. Then, Self-confidence is a psychological factor which plays a supportive role in speaking performance. The current study was aimed to know whether there is a significant correlation between self-confidence and speaking performance. The researcher used quantitative approach in which correlation research design was used. The total number of participants was of 30 students from the fourth semester of English Department.  To obtain the data, the researcher used Confidence in Speaking English as a Foreign Language (CSEFL) questionnaire in order to know the students’ level of self-confidence and speaking performance score was used to measure the level of the students speaking performance. The finding of the present study showed that the r observed of the students’ self-confidence and speaking performance was .261 with level of significance was .163 which is greater than .05. It means that the correlation between self-confidence and speaking performance was not significant. In other words, self-confidence cannot be used to predict the students’ speaking performance of the fourth semester students of English Department. To sum up the finding of the current study, the students with high self-confidence may have low speaking performance. Key word: correlation, self-confidence, speaking performance